A Study of Needs Analysis of Education at Undergraduate Level : EFL Case Study (International Journal of Psychosocial Rehabilitation, 2020)
This study investigates issues influencing the effective supplementary English as Second Language (ESL) programs at Pakistani tertiary institutions. The dearth of a recognizable curriculum framework at most universities and the absence of consistent faculty development tend to compromise the quality of ESL courses. With existing teacher training programs providing little exposure to curricular development, and the teachers’ academic qualifications not contributing to curricular creativity, the lack of follow-up means that the implemented curriculum diverges significantly from the official curriculum document. Focusing primarily on the textbooks and assessment, the classroom teachers do not take into account the educational objectives, and no evaluation of the implemented curriculum is carried out. In this study, seven university ESL teachers working at universities were surveyed to collect data on their teaching/professional experiences, program evaluation procedures and learner needs assessment. Questionnaire data was collected from twenty university students enrolled in a university in Islamabad. Three ESL professionals with extensive experience in tertiary teaching and knowledge of curriculum design and development were also interviewed. The study confirmed that ESL faculty at Pakistani universities lacked training in curriculum design and that needs assessment was arbitrary and informal.